2014
DOI: 10.1186/2193-1801-3-120
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis and apoptotic index as prognostic factors in non-small cell lung carcinoma: a review

Abstract: Necrosis and apoptosis represent two pathogenetically distinct types of cell death. Necrosis is associated with pathologic conditions while apoptosis is a physiological process of programmed cell death, which is associated with normal tissue growth and is frequently impaired in various forms of cancer. Tumor necrosis and apoptotic index (AI) have been previously evaluated as prognostic biomarkers in lung cancer, but their exact clinical value remains unclear. The aim of this study was to perform a systematic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…We have found that sorafenib causes massive cell death with typical “ghost” cells in some large solid tumors [16]. Everolimus or everolimus plus sorafenib also causes massive cell death but to a much smaller extent.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have found that sorafenib causes massive cell death with typical “ghost” cells in some large solid tumors [16]. Everolimus or everolimus plus sorafenib also causes massive cell death but to a much smaller extent.…”
Section: Discussionmentioning
confidence: 88%
“…Everolimus or everolimus plus sorafenib also caused massive cell death but to a much smaller extent (Figure 8). The dying or dead cells exhibited features of anucleate ghost cells characteristic of necrosis [16]. Greatest cell death was found for the sorafenib-only group (Table 1) ( P  = .002).…”
Section: Resultsmentioning
confidence: 93%
“…Bu çalışmaların sonuçları tekstür analizi bulgularının hasta prognozu ile ilişkili olduğunu işaret etmektedir (58,59). KHDAK'sinde özellikle hipoksiye bağlı olarak gelişen tümör nekrozu ve buna bağlı tümör içi heterojenite sık rastlanan bir histopatolojik özellik olup, primer tümörün yüksek derecede heterojeniteye sahip olmasının hastalık nüksü, tedavi direnci ve düşük sağkalım oranları ile ilişkili olduğu gösterilmiştir (54,60,61).…”
Section: Fdg Pet/bt Bulgularının Sayısal Analiziunclassified
“…The value of apoptotic index (AI) in diagnosis or prognosis has been studied in many cancer types (Becker et al, 2014, Fu et al, 2014, Gkogkou et al, 2014, Kuriyama et al, 2002, Ribeiro Mde et al, 2004, Richter et al, 2002, Wu et al, 2013, but the results were controversial. Further, AI was investigated as a predictor of chemotherapy response in gastric carcinoma (Jia et al, 2012, Wu et al, 2014a or radiotherapy response in cervical cancer (Bhosle et al, 2005), and breast cancer (Burcombe et al, 2005).…”
Section: Diagnostic Implicationsmentioning
confidence: 99%